Maximizing efficiency and ensuring safety: exploring the outcomes of 2 consecutive open radical cystectomies by the same team within a single surgical day - Egen, Luisa; Wessels, Frederik; Quan, Allison; Westhoff, Niklas Christian; Kriegmair, Maximilian; Honeck, Patrick; Michel, Maurice Stephan; Kowalewski, Karl-Friedrich (Urologic oncology, 2024)
Background - The purpose of this study was to evaluate the outcomes of performing 2 consecutive open radical cystectomies (RCs) within 1 day by the same surgical team. - Patients and Methods - A retrospective analysis was conducted on data from patients who underwent RC at a single tertiary care center from January 2015 to February 2023. Patient characteristics, perioperative outcomes and endpoints were analyzed. Univariable and multivariable logistic regression models were created to predict major complications. - Results - A total of 657 patients were included in the final cohort, containing 64 paired RCs (32 RC1 and 32 RC2) and 593 single RCs. Major complications occurred in 24.7% of the entire cohort, with no significant differences between single RC vs. RC1 and RC2. Paired RCs showed significantly shorter operative time (OT; p=0.001) and length of stay (LOS; p=0.047) compared to single RCs. There were no significant differences in transfusion rates, 30-day readmission, 30-day mortality, or histopathological results between paired and single RCs. Multivariable analysis identified patient characteristics such as age (OR=1.67, p=0.03), sex (OR=0.45, p=0.008), BMI (OR=1.98, p=0.007), ASA-score (OR=1.61, p=0.04), and OT (OR=1.87, p=0.008) as independent predictors of major complications. - Conclusion - Performing 2 consecutive open RCs within 1 day by the same surgical team is a safe approach in experienced hands. This strategy optimizes the utilization of surgical resources and addresses the growing demand for urologic care while maintaining high-quality patient care. Preoperative planning should consider patient-specific factors to minimize risks associated with major complications. - Micro Abstract - This study evaluates the outcomes of performing 2 consecutive open radical cystectomies (RC) in a single day by the same surgical team. Data from 657 patients who underwent RC at a single tertiary medical center proved that this approach is safe, with no significant differences in major complications. Preoperative planning should consider patient-specific factors for efficient utilization of surgical resources.